Analysis of Waste in Finished Feed Product Warehouse Using Lean Warehouse Approach - Pratiwi Candra Kurniawati Yolanda; Dira Ernawati (ITEJ (Information Technology Engineering Journals), 2026)
Inefficient warehouse operations often generate various forms of waste, including excessive waiting times, unnecessary transportation, and redundant activities, which ultimately increase lead times and reduce operational performance. Despite the critical role of finished feed product warehouses in maintaining supply chain responsiveness, studies addressing waste reduction in this context remain limited. This study aims to identify non-value-added activities in the finished feed product warehouse process and propose improvement strategies to enhance warehouse efficiency using a Lean Warehouse approach. The study integrates Value Stream Mapping (VSM), Value Stream Analysis Tools (VALSAT), fishbone diagram analysis, and the 5W+1H method to systematically identify, analyze, and eliminate waste within warehouse operations. The findings reveal that the current warehouse process has a total lead time of 447 minutes. Following the implementation of the proposed improvements, the future-state lead time is reduced to 269 minutes, representing a 39.8% reduction. In addition, Process Cycle Efficiency (PCE) improves from 20.81% to 34.57%, indicating a 13.76 percentage-point increase in operational efficiency. The identified improvements primarily address delays, excessive movement, and procedural redundancies in the warehouse flow. These results demonstrate that the Lean Warehouse approach provides an effective framework for minimizing waste and improving the performance of finished feed product warehouses. The study contributes practical insights for warehouse managers seeking to enhance operational efficiency and supports the broader application of lean principles in warehousing environments.